EVALUATION OF HEARING CONSERVATION PROGRAM IN PT PAITON OPERATION AND MAINTENANCE INDONESIA (PT POMI) - Afina, Yoriza Mirsa; Widajati, Noeroel; Ashr, Roiyan Mumtaz Fathul; Imaduddin, Ahmad (HEARTY, 2025)
Introduction: The regulations related to hearing conservation programs are currently still theoretical and not practical. In the production process at PT POMI, there are several pieces of equipment that serve as sources of noise in the work area. Based on data from measurements of the work environment related to noise in the work area and noise exposure measurements on representative workers, the results indicate that the highest noise exposure at PT POMI is 97.9 dBA. Method: This research is a descriptive study that provides an overview of the implementation of the hearing conservation program. Data collection was conducted through observation, interviews, and literature review. The data obtained is then discussed by comparing it with existing regulations. Result: PT Paiton Operation and Maintenance Indonesia has implemented all elements of the hearing conservation program in accordance with the regulatory requirements of the Occupational Safety and Health Administration (OSHA) No. 1910.65 regarding Occupational Noise Exposure. Conclusion: PT POMI has implemented six elements of the hearing conservation program including noise exposure monitoring; engineering and administrative controls; audiometric test; hearing protection devices; training and education; and record keeping. However, the implementation of these elements has not been fully maximized.